PENGEMBANGAN EKONOMI KREATIF DAN PPKN DI SMA MEMBANGUN JIWA WIRAUSAHA DAN INTEGRITAS GENERASI MUDA - Monalisa Siahaan; Martogu S Sinambela; Daniel Pasaribu; Grace Ester Sitio; Adelia Sitompul (CV SWA Anugerah, 2025)
This community service activity aims to build an entrepreneurial spirit and instill integrity values ​​in high school students through a creative economy approach and strengthening PPKn subjects. This program was implemented at SMA Swasta TAMANSISWA Lubuk Pakam during February 2025. The implementation method uses a project-based and participatory learning approach. This activity has been proven to increase students' understanding of the concept of the creative economy, improve skills in designing business ideas, and form student business groups that uphold PPKn values ​​such as honesty, responsibility, and mutual cooperation. These results indicate that the integration of the creative economy and PPKn is effective in forming a young generation that is entrepreneurial and has character.